Toward the elimination of hepatitis B: networking to promote the prevention of vertical transmission of hepatitis B virus through population-based interventions and multidisciplinary groups in Africa - Torimiro, Judith Ndongo Embola; Duri, Kerina; Goumkwa, Nadège M.; Atah, Solange M.; Ndzie Ondigui, Juliette-Laure; Lobe, Cindy; Bouyou, Marielle; Ndeboko, Bénédicte; Mahamat Moussa, Ali; Police, Camengo; Awoumou, Patrick; Peyonga, Puinta; et al. (Frontiers in Public Health, 2024)
brings evidence to support government strategies in the elimination of hepatitis B. Hepatitis B is caused by hepatitis B virus (HBV) and it is transmitted from mother-to-child (MTCT). Few countries in Africa implement an effective national Programme for the prevention of MTCT of HBV (PMTCT) as in the case of HIV. The MICHep B Network (mother-infant cohort hepatitis B) was created in 2018 of volunteers from professional groups and the civil society in Cameroon, Chad, Central African Republic, Gabon, and Zimbabwe. This South-South initiative is to promote PMTCT of HBV interventions. Vaccination against hepatitis B at birth (HepB-BD) is an effective way to prevent HBV from mother-to-child. However, 14 countries in WHO Africa Region had incorporated HepB-BD vaccine in the national vaccination Programme, and only one in the MICHep B Network by end of 2022. To contribute to country strategies in the fight against hepatitis B, the MICHep B network has implemented in-depth interviews with health personnel, capacity-building workshops, sensitization campaigns and serosurveys for pregnant women and the community on methods of transmission and prevention of HBV. These cost-effective community involvement interventions can be scaled-up in other settings to support the incorporation of hepB-BD vaccine in national immunization Programmes.